Baseline and on-treatment markers determining prognosis of first-line chemotherapy in combination with bevacizumab in patients with metastatic colorectal cancer - Quidde, Julia; Kripp, Melanie (Oncology research and treatment, 2017)
Background: In metastatic colorectal cancer, no upfront or on-treatment markers are available to determine the prognosis or efficacy for chemotherapy in combination with bevacizumab. Patients and Methods: The current analysis was performed to evaluate the prognostic value of disease and patient characteristics (age, number of metastatic sites, stage of primary tumor, performance status, carcinoembryonic antigen (CEA)) and on-treatment changes of CEA (response after 8-12 weeks of treatment and specific patterns of CEA kinetics) in patients from an observational cohort study of chemotherapy with bevacizumab. Results: Baseline factors were available from 1,438 patients. Patients with baseline CEA levels > 20 ng/ml, more than 1 metastatic site, and age > 75 years showed significantly lower progression-free (PFS) and overall survival in multivariate analysis. A CEA response of > 30% during treatment was associated with increased PFS. In addition, the pattern of CEA kinetics predicts survival and response to treatment. Conclusion: In summary, baseline CEA, number of metastatic sites, and age are strong independent prognostic factors for survival. By monitoring CEA, clear patterns with distinct prognostic value can be determined. CEA kinetics and/or response after 8-12 weeks might be a useful and simple tool to stratify the post-induction treatment approach based on individual prognosis in the future.